Dysfunction in fatty acid amide hydrolase is associated with depressive-like behavior in Wistar Kyoto rats. - K Yaragudri Vinod (Public Library of Science (PLoS), 2012)
Background While the etiology of depression is not clearly understood at the present time, this mental disorder is thought be a complex and multifactorial trait with important genetic and environmental contributing factors. Methodology/principal findings The role of the endocannabinoid (eCB) system in depressive behavior was examined in Wistar Kyoto (WKY) rat strain, a genetic model of depression. Our findings revealed selective abnormalities in the eCB system in the brains of WKY rats compared to Wistar (WIS) rats. Immunoblot analysis indicated significantly higher levels of fatty acid amide hydrolase (FAAH) in frontal cortex and hippocampus of WKY rats with no alteration in the level of N-arachidonyl phosphatidyl ethanolamine specific phospholipase-D (NAPE-PLD). Significantly higher levels of CB1 receptor-mediated G-protein coupling and lower levels of anandamide (AEA) were found in frontal cortex and hippocampus of WKY rats. While the levels of brain derived neurotropic factor (BDNF) were significantly lower in frontal cortex and hippocampus of WKY rats compared to WIS rats, pharmacological inhibition of FAAH elevated BDNF levels in WKY rats. Inhibition of FAAH enzyme also significantly increased sucrose consumption and decreased immobility in the forced swim test in WKY rats. Conclusions/significance These findings suggest a critical role for the eCB system and BDNF in the genetic predisposition to depressive-like behavior in WKY rats and point to the potential therapeutic utility of eCB enhancing agents in depressive disorder.